Taxonomic revision of the cavefish genus Karstsinnectes (Cypriniformes, Nemacheilidae), with a description of a new species from Guangxi Province, China - Ge, Jia-Yue; Nong, Zheng-Quan; Yang, Jian; Du, Li-Na; Zhou, Jia-Jun (Zoosystematics and Evolution, 2024)
The blind cavefish genus Karstsinnectes , established in 2023, is the subject of taxonomic revision in the present study. Five valid species are recognized, including one new species, Karstsinnectes longzhouensis sp. nov. , described from Guangxi, China, based on a combination of morphological evidence. Karstsinnectes longzhouensis sp. nov. can be distinguished from all other congeners based on the presence of a lateral line, 11–12 branched pectoral fin rays, and five branched pelvic fin rays. Additionally, due to the loss of the type specimens, a neotype is designated for K. parvus . The lateral line of K. hyalinus is revised as lacking in this study. A key to all valid Karstsinnectes species is provided. Blind cavefish serve as a valuable natural framework for investigating convergent and adaptive evolutionary processes. The survival of cavefish is under significant threat due to human activities, climate change, water pollution, and invasive species. Thus, to preserve these valuable species, it is crucial to implement various conservation measures, such as habitat protection, artificial breeding, and fundamental research.